ANALYSIS OF MONETARY POLICY ON ECONOMIC GROWTH IN INDONESIA DURING THE OUTBREAK OF COVID-19 - Wahyuni, Amalia (Program Doktor Ilmu Ekonomi, 2022)
Monetary policy is a policy of Bank Indonesia aimed at managing a country's money supply in order to achieve certain objectives such as maintaining monetary stability and increasing employment opportunities. The analysis of monetary policy in Indonesia aims to discover and anticipate the impact of the Covid-19 pandemic on the Indonesian economy. Research uses descriptive qualitative research methods that include different concepts in the research process using content analysis techniques as well as literature search. The results of this study show the monetary policy efforts of the Indonesian government to stabilize the economic system, supported by Bank Indonesia through the role of the Financial Services Authority in Indonesia. At that time, the Indonesian government tried to implement this policy to relieve the Indonesian nation of the economic crisis due to Pademi Covid 19, which has an even greater impact. Keywords : Monetary Policy, Inflation, Money Suppy, Interest Rates, Exchange Rates, GDP (Gross Domestic Product), Economic Growth